Containment and conversion: urban livelihoods and the circulation of value amid South Africa's avian influenza outbreak - Cousins, T; Pentecost, M; van Helden, L (American Anthropological Association, 2022)
In South Africa the racialized contours of economic life powerfully shape the distribution of who owns poultry enterprises, who is employed to labor in them, who consumes poultry products, and in which way. When, in late 2017, an outbreak of highly pathogenic avian influenza (H5N8) decimated the South African poultry sector, it revealed the ontological transformations of industrial egg-laying poultry into “cull birds” and then into imileqwa, the quintessential rural chicken. It thus showed how distinct regimes of value “articulate,” blurring infectious and noninfectious concerns as new chains of conversion were inaugurated across domestic and global economies. Thanks to the mediations performed by the network of egg-laying chickens, (White) farmers, (Black African) consumers, and state veterinarians, translations of value take place in which industrialized egg-layer chickens turn into socially enlivened beings. Such beings sustain and nurture social reproduction in South Africa's postapartheid cities and beyond.